THE CONSTRUCTION OF LEARNING ACTIVITY PACKAGE BASE ON PROBLEM BASE LEARNING FOR WORD PROBLEM SOLVING IN LINEAR EQUATION FOR MATHAYOMSUKSA 1 OF BANCHANGKARNCHANAKULWITTAYA SCHOOL - Daosue, Jenjira; Chaiworn, Areeruk; Lertprapai , Satinee (Journal of Educational Review Faculty of Education in MCU, 2020)
The purposes of this research were 1) to create of learning activity package base on problem base learning for word problem solving in linear equation for Mathayomsuksa 1 students to be effective in accordance with specified criteria, 2) to study the academic achievement on word problem solving in linear equation for Mathayomsuksa 1 students after using the activity package base on problem base learning, 3) to study the satisfaction of Mathayomsuksa 1 students towards using the activity package base on problem base learning. This research was an experimental research based on one-group test after learning with a statistic criterion. The research instruments were 1) Problem-based learning management plan, 2) learning activity package of problem base learning, 3) achievement test of word problem solving in linear equation, and 4) the satisfaction questionnaires of Mathayomsuksa 1 students. Data were analyzed using descriptive statistics consisted of mean, standard deviation, and t-test. Results showed that 1) the learning activity package base on problem base learning for word problem solving in linear equation for Mathayomsuksa 1 students with a required efficiency value of 81.04/76.20. 2) the academic achievement on word problem solving in linear equation for Mathayomsuksa 1 students after using the activity package base on problem base learning was statistically higher than criterion the 70 percentage was statistically significant at .05. 3) the satisfaction of students towards the learning packages a higher level equal 70.80 percent.